Analisis Kontribusi Sektor Perhubungan terhadap Pendapatan Asli Daerah di Kabupaten Aceh Tengah - Ramadayani, Ravika; Nasution, Irwan; Matondang, Armansyah (PERSPEKTIF, 2018)
The function of regional autonomy is to regulate and manage government affairs in the region, the implementation of regional autonomy has an important influence for each region to be more creative in utilizing existing economic resources in the region for the successful implementation of development in the region. In this case the Central Aceh District Government seeks to explore the potential of funds that can increase Regional Original Revenue, one of which is from the Transportation sector. The problem that was formulated was "How is the development of the contribution of the Transportation Sector to the Original Regional Revenue (PAD) of Central Aceh District of Takengon City in 2016-2017. The purpose of this paper is to find out the magnitude of the development of contributions from each field and the Technical Implementation Unit (UPT) at the Department of Transportation to Regional Original Revenue in Central Aceh District. In this study the author uses descriptive methods with qualitative data analysis where researchers are key instruments, data collection techniques are done by triagulation (combined). Based on the discussion, it can be concluded that, revenues from the transportation sector collected ?from ?each ?Field ?and ?Technical ?Implementation ?Unit ?(UPT) ?in ?the ?Transportation Agency within 2 years tend to decline from the previous year, which only increased from the results of parking service fees on the edge of public roads and regional wealth usage levies.?